Cooperation of mitochondrial and ER factors in quality control of tail-anchored proteins - Dederer, Verena; Khmelinskii, Anton; Huhn, Anna Gesine; Okreglak, Voytek; Knop, Michael; Lemberg, Marius (eLife, 2019)
Tail-anchored (TA) proteins insert post-translationally into the endoplasmic reticulum (ER), the outer mitochondrial membrane (OMM) and peroxisomes. Whereas the GET pathway controls ER-targeting, no dedicated factors are known for OMM insertion, posing the question of how accuracy is achieved. The mitochondrial AAA-ATPase Msp1 removes mislocalized TA proteins from the OMM, but it is unclear, how Msp1 clients are targeted for degradation. Here we screened for factors involved in degradation of TA proteins mislocalized to mitochondria. We show that the ER-associated degradation (ERAD) E3 ubiquitin ligase Doa10 controls cytoplasmic level of Msp1 clients. Furthermore, we identified the uncharacterized OMM protein Fmp32 and the ectopically expressed subunit of the ER-mitochondria encounter structure (ERMES) complex Gem1 as native clients for Msp1 and Doa10. We propose that productive localization of TA proteins to the OMM is ensured by complex assembly, while orphan subunits are extracted by Msp1 and eventually degraded by Doa10.